Adjustable facade handling track / Suaidah Shima Shahrin - Shahrin, Suaidah Shima (2021)
Material handling refers to the delivery, movement, safety, storage, or control of materials. Today, Material handling been one of the most critical part on the high-rise construction. The aim of this study is to investigate the problem of handling façade on a high-rise building and to invent innovation product that are better and safer. The study adopts several data collection tools to collect data to gain reliable information on the innovation idea such as questionnaire survey and literature review from the primary and secondary data collection. The study found that current facade handling was having problem with wind sensibility and safety issue. From the result, an innovation idea of the Adjustable Façade Handling Track was created to encounter the problems identified that has been occurred during the façade handling work. Besides, the performances of the Adjustable Façade Handling Track were expected to provide better workability . However, it is recommended to improve the safety features by install rubber stopper on the side of I beam trolley and I beam to avoid from out of track to improve the equipment performance.